Pedagogical Insights into Classroom Instruction Practices of English Language Teacher Training (ELTT) Teachers in South Kalimantan - Nani Hizriani; Hidayah Nor; Khairatunnisa Khairatunnisa (Jo-ELT (Journal of English Language Teaching) Fakultas Pendidikan Bahasa & Seni Prodi Pendidikan Bahasa Inggris IKIP, 2025)
Classroom instruction involves how teachers deliver lessons, engage students, and convey information and also involves pedagogical considerations to support students' learning. This study investigates the instructional practices employed by English Language Teacher Training (ELTT) teachers in South Kalimantan. Through a mixed-method sequential explanatory design encompassing depth semi structured interview and non-participant classroom observation, the study explores 19 ELTT Madrasah teachers in South Kalimantan. The findings shed light on the teachers' ways in giving instruction such as the preparation before the instructions, teachers write the instruction for developing lesson plan, arrange the classroom and grouping the students, getting students' attention and communicating lesson goals, the time for instruction, language choices, classroom activities, modelling the activities, using extra-linguistics devices, checking students' understanding and monitoring students' activities. ELTT Program also shape the instructional practices of teachers in terms of their preparation, the use of more English as a medium of instruction, their engagement with technology, their confidence and creativity, and more students’ participation. This study contributes valuable insights to the realm of language education, offering implications for teacher development and improved student outcomes in South Kalimantan.